International establishment mode, ownership structure, and performance of emerging economy MNES: enriching the global value chain perspective with the institution-based view - Yang, Tianle (2020)
By adopting a global value chain (GVC) perspective and institution-based view, this study examined three key issues of emerging market multinational enterprises (EM MNEs) as they conduct foreign investments: 1) determinants of the decision made concerning the mode of establishment, greenfield or acquisition; 2) determinants of the choice of ownership structure, whole ownership or share ownership; and 3) the impact of mode choices on firms’ foreign subsidiary performance.